Comparison between clinical and radiographical detection of proximal dental caries among adult patients attending International Islamic University Malaysia Dental Clinic - Abdul Majeed, Kais Raad; Yahaya, Nur Hanis; Raja Sulaiman, Raja Sarah (EuroJournals Publishing, Inc., 2012)
Objective: The aim of this research is to compare the clinical and radiographical findings of proximal dental caries among adult patients attending IIUM Dental Clinic. Methods: The method was prospective cross sectional study that was conducted on 69 adult patients attending IIUM Dental Clinic. For each patient, clinical charting was done first without using radiograph by using double blind technique. After that bitewing radiograph were taken. The radiograph was viewed from the computer and was assessed for any radiolucency below the contact point either at mesial or distal part of the tooth. When there was radiolucency present in the radiograph, the data were recorded even clinically cannot be seen. Results: Results revealed that from 69 patients, 171 teeth were detected with proximal dental caries. Out of 171 teeth with proximal dental caries, 133 teeth were detected by both clinically and radiographically while 38 teeth were detected by radiographically only. Conclusion: As a conclusion, there is significant different between clinical and radiographical of proximal dental caries detection (P<0.05)